2020
DOI: 10.3390/healthcare8030247
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Type 2 Diabetes Risk and Its Effect Evaluation Based on the XGBoost Model

Abstract: In view of the harm of diabetes to the population, we have introduced an ensemble learning algorithm—EXtreme Gradient Boosting (XGBoost) to predict the risk of type 2 diabetes and compared it with Support Vector Machines (SVM), the Random Forest (RF) and K-Nearest Neighbor (K-NN) algorithm in order to improve the prediction effect of existing models. The combination of convenient sampling and snowball sampling in Xicheng District, Beijing was used to conduct a questionnaire survey on the personal data, eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 20 publications
2
57
0
1
Order By: Relevance
“…Our study showed XGBoost performed best when predicting microbial sources in two categories. The result is not surprising as other studies have shown that XGBoost has advantages over other models ( Pan, 2018 ; Wang et al, 2020 ). Similar to Random Forest, it is an ensemble method that makes inferences based on multiple decision trees, thus reducing prediction errors.…”
Section: Discussionmentioning
confidence: 50%
“…Our study showed XGBoost performed best when predicting microbial sources in two categories. The result is not surprising as other studies have shown that XGBoost has advantages over other models ( Pan, 2018 ; Wang et al, 2020 ). Similar to Random Forest, it is an ensemble method that makes inferences based on multiple decision trees, thus reducing prediction errors.…”
Section: Discussionmentioning
confidence: 50%
“…These parameters include the number of boosting stages to perform (n_estimators), the maximum depth of a tree (max_depth), the minimum sum of instance weight required in a child (min_child_weight), the subsample ratio of the training instances (subsample), the random seed given to each estimator at each boosting iteration (random_state), and the rate of learning from training data (learning_rate). Similar XGBoost hyperparameter tuning has been done by the authors of the study [65].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, in the case of methods such as deep learning, one cannot understand the decision-making process within the algorithm. Thus, it is hard to make grounded implications for medical purposes when multiple causes are at play [ 27 ].…”
Section: Discussionmentioning
confidence: 99%